Foundation forum: developing leadership skills among foundation trainees. (2nd April 2019) - Kadhum, Murtaza; Sinclair, Pierre; Narshi, Chetan
Abstract : Foundation forums have been adopted over the last few years to provide representation for newly qualified doctors, but they do not develop essential leadership, management and quality improvement skills for those recruited – key attributes that have been formally identified byGeneral Medical Council (2012) guidance. A foundation forum was set up across three Oxford deanery hospitals. Forum members were assigned classical forum roles, but were also tasked to complete quality improvement projects, organize a national quality improvement conference, and undergo formal leadership and management training. Members were surveyed before and after completion of training, revealing statistically significant increases in confidence in leadership, management and quality improvement skills. All members revealed an eagerness to continue formal leadership and management training. The foundation forum proved a successful initiative to improve overall trainee experience and involvement, while providing a platform for leadership and management training to satisfy key domains within the Medical Leadership Competency Framework.